Stevia rebaudiana, Oligofructose and Isomaltulose as Sugar Replacers in Marshmallows: Stability and Antioxidant Properties. Issue 4 (3rd December 2015) - Periche, Ángela; Castelló, María Luisa; Heredia, Ana; Escriche, Isabel
Abstract: Consumers are increasingly demanding products with natural ingredients and functional properties. The replacement of conventional sugars with recently available sugars or sweeteners could result in the perception of candies as healthier products. Therefore, the objective of this work was to evaluate the influence of isomaltulose, oligofructose and stevia extracts on the physicochemical, mechanical, optical and antioxidant properties as well as the shelf life of marshmallows. A sensory test was carried out in order to evaluate the influence of these ingredients on the acceptance of this product. The instrumental and sensorial textural results indicate that the sucrose and glucose syrup in commercial marshmallows could be replaced by a mixture of isomaltulose, oligofructose and stevia. Adults found the new and the traditional marshmallows to be very similar. However, children only found similarities in terms of the texture. These new marshmallows, besides being more microbiologically stable, have added value due to their antioxidant properties. Practical Applications: Society is becoming increasingly aware of the importance of nutrition in health, and this has a decisive impact on the proposals of the candy sector in terms of innovation and new product development. The main trends of the market are focused on eliminating the unhealthy ingredients in the formulations, such as sugars, and even incorporate active ingredients with functional properties, but without forgetting customer satisfaction. At present, the industry is using both intense and volume artificial sweeteners as conventional sugar substitutes. However, the food industry now has the possibility of using alternative natural sweeteners such as stevia, oligofructose and isomaltulose, with the added value of providing certain healthy benefits. The results of the present study could provide pertinent information to the confectionary industry that wishes to take on the challenge of developing candies with functional ingredients.